Fiction and Reality: The Impact of Layoff on Family Structure - Ozcan, Kerim (European Scientific Journal, ESJ, 2017)
Post-capitalist economy, which is characterized by conditions such as high competition, global circulation of capital and neo-liberal regime, forced organizations to introduce novel types of organizing strategies that aim to promote efficiency and effectiveness. Organizations tend to follow restructuring, downsizing or subcontracting strategies to become more â€œcompetitiveâ€ that causes high number of laid off and displaced employees. This fact of job loss is strikingly handled by two films. Inspired from these two films, the present study aims to argue the negative impacts of job loss on family. For this aim, in-depth interview was conducted with 8 laid off employees. Findings indicate that long-run unemployment is destructive on family structure. Separation and intent of separation of couples increase by the paternal job loss that also creates role inversion between the partner that results in self-esteem and mental health erosion of patriarch.